قرآن مجید کی روشنی میں سیرت نگاری کا رجحان اور اس منہج کے حامل اردو ادب سیرت کا تعارف: Trend of Seerah Writing in the light of Quran and introduction of Urdu Seerah Litterature of this methodology - Dr. Hasaam ul Deen; Dr. Muhammad Sajjad (MEI, 2023)
Biographers of the Holy Prophet (Peace Be Upon Him) had always been there in every era. Books on the holy life of the holy prophet (PBUH) were written in all the known languages. The biographers analysed his (PBUH) holy life, keeping in view different citations and angles. Thus, various styles of biography of the Holy Prophet (PBUH) came into being in accordance with the epoch, locale, necessity, disposition and attitude along with procedural method. In these diverse styles of biography, there is a modern trend in the style of biography of Holy Prophet (PBUH) in the light of the Holy Quran. This trend started in the first quarter of 20th century A.D. A great number of books bearing this style are available in the top two most spoken languages in the world, those are, Arabic and Urdu.Maulana Abu Al-kalam Azad and Maulana Syed Abu Al'A’la Maududi, among the Urdu biographers of the Holy Prophet (PBUH), guided towards this style. Whereas, according to Dr Mehmood Ahmed Ghazai, Allama Muhammad Iqbal too, drew attention towards this style. The wish to portray the Holy Qur’an and the holy life of the Qur’an possessor (PBUH) together, an attempt to confide, popularize and authenticate the literature, abandonment of Ahadith and narrations of the biography of the Holy Prophet (PBUH), and the presence and search of scores of material about the biography of the Holy Prophet (PBUH) present in the Holy Qur’an, are among the major motives in the trend of writing Quranic biography of the Holy prophet (PBUH).Under the trend of writing Quranic biography of the Holy Prophet (PBUH), a great number of books written in Urdu, are available. In some of these books, the writers gathered, translated and annotated those verses of the Holy Quran that carry his (PBUH) attributes, perfection, miracles, battles and following the commandments. Whereas some biographers tried to narrate the life of the Holy Prophet (PBUH) in continuity. Under this trend, among the biographers of the Holy Prophet (PBUH), knowledgeables are also there, having the same point of view from Islam. And deviating men of letters are also included in the list who declared the narrarations of the biography of the Holy Prophet (PBUH) and the collections of the Ahadith suspicious.This article bears the start and evolution of the trend of Quranic biography of the Holy Prophet (PBUH). And assertion of the motives, along with the brief introduction and analysis of almost 44 books containing such a style of biography, is also included.